"The Glory of God Is Intelligence": Exploring the Foundations of Latter-day Saint Religious Education. Issue 2 (14th March 2016) - Griffiths, Casey Paul; Esplin, Scott C.; Randall, E. Vance
Abstract: In recent years the educational programs of the Church of Jesus Christ of Latter-day Saints (LDS) have received praise for their role in the high rates of religiosity and denominational retention among their youth. This study offers a historical summary of the efforts of LDS to develop the most effective methods of engaging their youth in religious education. It tracks the development of LDS religious education from its origins in the United States, to its efforts on the global stage. Ultimately, LDS educators adopted a flexible approach utilizing volunteer teachers to meet the needs of this growing global faith.